Analisis Prinsip dan Faktor Produksi dalam Ekonomi Islam pada “Muza Konveksi” di Kecamatan Sumberpucung, Kabupaten Malang - Ana Nurwakhidah; Mamlu’atul Munawaroh (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2023)
In economic activities known as production activities, producers contribute to the creation of goods. This production activity's goals are to satisfy consumer demand and generate profits for the producers. In Islamic economics, production refers to any actions taken to achieve or enhance profits by utilizing the sources of gain supplied by Allah SWT to meet the requirements of the community. As a result, production efforts must be focused on meeting these demands. The main topic of this study is how